Computer numerical control : essentials in programming and networking - Lin, Su-Chen Jonathon. (Delmar, 1994)
This book is divided into five parts: Essentials of CNC technology; Manual CNC programming; Computer-Assisted programming in APT; CAD/CAM NC Programming; CNC Networking.